Deep Disagreements in the Post-Truth Era (Andamios, Revista de Investigación Social, 2026)
This paper explores the relationship between post-truth and deep disagreements. It argues that the post-truth era distorts and modifies our experience of deep disagreements by presenting some of the specific ways in which this occurs. In the first section, the current discussion about deep disagreement and its rational resolution is outlined. The second section deals with some characteristics of the post-truth era. Finally, the third section raises different ways in which our experience of deep disagreement can be distorted in an era characterized by post-truth features, such as the present one.
Keywords: Post-truth; deep disagreements; rational resolution; disinterest in the truth; rational persuasion